Random mappings with a single absorbing center and combinatorics of discretizations of the logistic mapping. (1999) - Klemm, A.; Pokrovskii, A.
Abstract : Distributions of basic characteristics of random mappings with a single absorbing center are calculated. Results explain some phenomena occurring in computer simulations of the logistic mapping.